Development of a CYP2D6-enhanced HepaRG cell model with improved CYP2D6 metabolic capacity - Chizuka Obara; Yohei Iizaka; Akari Mine; Yojiro Anzai; Masako Tada; Shinpei Yamaguchi (PLoS ONE, 2025)
Drug-induced liver injury is a major concern in drug development, and the limitations of animal models have driven interest in human-derived in vitro models for toxicity assessment. HepaRG cell-based liver models are promising due to their ability to differentiate into hepatocyte-like cells that highly express Cytochrome P450 (CYP) 3A4; however, their low CYP2D6 expression limits their utility in representing human liver metabolism. CYP2D6 is a polymorphic enzyme responsible for inter-individual variability in drug metabolism and is associated with adverse drug reactions. To address this limitation, the present study aimed to enhance CYP2D6 expression in undifferentiated HepaRG cells, successfully generating multiple transgenic cell lines with varying levels of CYP2D6 activity. We developed FLAG-tagged CYP2D6 and IRES-green fluorescent protein (GFP)-co-expressing CYP2D6 HepaRG cells, enabling CYP2D6 expression to be monitored via FLAG and GFP signals. These cells exhibited a remarkable 5- to 8,000-fold increase in CYP2D6-mediated bufuralol metabolism. Notably, the CYP2D6 expression level in a CYP2D6-iGFP cell line was comparable to that observed in human liver tissue. Furthermore, enforced CYP2D6 expression showed a tendency to reduce the cytotoxicity of perhexiline, a drug primarily metabolized by CYP2D6. Among the five transgenic cell lines we developed, two cell lines retained the differentiation potential of HepaRG cells, giving rise to CYP3A4-positive hepatocyte-like cells. Moreover, we demonstrated that CYP2D6-iGFP HepaRG cells retain transgene expression following differentiation into hepatocyte-like cells in vitro . While some transgenic HepaRG cell lines exhibited limited differentiation potential, the CYP2D6-enhanced cells will serve as an effective cell model for in vitro studies of drug metabolism and toxicity, especially for compounds that are metabolized by CYP2D6.